In vitro and in vivo Activity of K-130, a Dihydrofolate Reductase inhibitor, against Mycobacterium leprae - Dhople, Arvind M. (Arzneimittelforschung, 1999)
The antimicrobial effects of a new dihydrofolate reductase inhibitor, K-130 (2,4-diaminodiphenyl sulfone substituted 2,4-diamino-5-benzylpyrimidine), alone and in combination with dapsone (CAS 80-08-0) against both dapsone-sensitive and dapsone-resistant strains of Mycobacterium leprae were evaluated in vitro, in cell-free culture system, and in vivo, in mouse foot pads. The minimal inhibitory concentration of K-130 against dapsone-sensitive as well as dapsone resistant strains of M. leprae was 0.03 μg/ml, and the activity was bactericidal in both cases. However, when combined with dapsone, K-130 exhibited synergism in case of dapsone-sensitive M. leprae, while in case of dapsone-resistant M. leprae, the effect was merely additive. Similar synergistic effects were also observed in the mouse foot pad system for both types of M. leprae strains.
Keywords: Antileprosy drugs; CAS 80-08-0; Dapsone; Dihydrofolate reductase inhibitor; K- 130, antimicrobial effects, combination with dapsone